Nitrotyrosine in brain tissue of neonates after perinatal asphyxia. Issue 6 (11th July 2006) - Groenendaal, F; Lammers, H; Smit, D; Nikkels, P G J
Abstract : Hypothesis: Nitrotyrosine, a reaction product of peroxynitrite and proteins, could be demonstrated in the postmortem examination of brain tissue of full-term neonates who had severe perinatal asphyxia. Methods: The brain tissue of 22 full-term neonates who died after severe perinatal asphyxia was examined, including cerebral cortex, basal ganglia, thalamus, hippocampus, brain stem, olives and cerebellum. Median age at death was 52 h. Routine histopathological examination and additional immunohistological staining were carried out with anti-cysteine protease protein 32 antibodies to detect activated caspase 3, anti-nitrotyrosine antibodies to detect nitrotyrosine and anti-CD68 antibodies to detect activated microglia and macrophages, which might be associated with the production of nitric oxide. Staining was scored as none, weak (1–25% positive cells), moderate (26–75% positive cells) or severe (>75% positive cells). Results: 14 patients showed global injury, 4 showed injury of the basal ganglia and thalamus, and 4 showed predominantly parasagittal brain injury. One neonate without perinatal asphyxia served as a control. Nitrotyrosine staining of neurones was shown in all neonates with asphyxia, mostly in the thalamus (70%) and inferior olives (68%). Total nitrotyrosine staining tended to be less in the base of the pons and inferior olives of neonates with parasagittal brain injury. Activated caspase 3 was found mostly in the thalamus (60%) and hippocampus (53%). Positive CD68 staining was mainly present in the thalamus (70% positive). Conclusion: Nitrotyrosine was found in brain tissue of full-term neonates, suggesting that nitric oxide toxicity might have a role in hypoxic–ischaemic brain injury at term. This may be relevant for neuroprotective strategies in full-term neonates with perinatal asphyxia.